Boron-substituted 1,3-dienes and heterodienes as key elements in multicomponent processes - Eberlin, Ludovic; Tripoteau, Fabien; Carreaux, François; Whiting, Andrew; Carboni, Bertrand (Beilstein Journal of Organic Chemistry, 2014)
In the last few years, multicomponent reactions involving boron substituted 1,3-dienes have emerged as important tools in synthetic organic chemistry. The most significant recent results and developments obtained in this area are reported in this review.
Keywords: allylboration; boron compounds; Diels–Alder; 1,3-dienes; multicomponent reactions; Petasis borono–Mannich; Suzuki couplings